Phytochemical content, antioxidants and cell wall metabolism of two loquat (Eriobotrya japonica) cultivars under different storage regimes - Minas, Ioannis S.; Kourdoulas, Panayiotis; Goulas, Vlasios; Vicente, Ariel Roberto; Manganaris, George A. (My University, 2014)
Changes in quality, phytochemical content and cell wall metabolism of two loquat cultivars (Eriobotrya japonica cvs. ‘Morphitiki’, ‘Karantoki’) under different storage regimes were studied. The fruit were harvested at commercial maturity stage and analyzed after 1, 3, 5, 7, and 11 days maintenance at room temperature (RT, ∼20 °C) or after cold storage (14 days at 4 °C) and additional ripening at RT for 1, 3 and 5 days, respectively. Compositional analysis revealed substantial cultivar differences; the ‘Morphitiki’ fruit was more acidic and showed higher contents of total phenolics, flavonoids and hydroxycinnamic acid-derivatives as well as greater antioxidant potency. Although firmness did not change markedly during storage, the cell wall exhibited extensive remodeling. Greater changes were observed in the pectin backbones than in polyuronide side chains and cross-linking glycans. Polygalacturonase (PG) showed better association with cell wall solubilization at RT than the enzymes involved in arabinan or galactan disassembly. During postharvest ripening after harvest, ‘Karantoki’ showed more extensive pectin solubilization than ‘Morphitiki’. Interestingly, cold storage inhibited the cell wall disassembly in ‘Karantoki’ but not in ‘Morphitiki’, suggesting that the cultivars may differ in their susceptibility to chilling-related wall disorders. Low temperature-induced alterations in wall disassembly may impact juice and phytochemical release upon consumption.
Keywords: Antioxidant activity; Cold storage; Chilling injury; Carotenoids; Flavonols; Phenolics; Ripening